Inovasi Kebijakan Publik Pemerintah Daerah DKI Jakarta dalam Mendorong Pertumbuhan Ekonomi Kreatif - Patria, Yoka Mai; Suwarta, Firdaus (Reformasi Administrasi, 2023)
The creative industry has the potential to generate unique products and services that are in demand both in the local and international markets. Public policy innovation becomes highly relevant. The local government of DKI Jakarta needs to develop policies that support the growth of the creative economy sector, such as providing adequate facilities and infrastructure, mentoring and training for creative industry players, as well as promoting and marketing local products. This study aims to analyze the effectiveness of public policy innovation implemented by the local government of DKI Jakarta in driving the growth of the creative economy. The research aims to examine the policies adopted by the local government and evaluate their impact on the growth of the creative economy sector in DKI Jakarta. The research method utilizes a qualitative descriptive approach with secondary data or literature review. The conclusion of this study is that the public policy innovation implemented by the local government of DKI Jakarta has a significant effectiveness in driving the growth of the creative economy. Through the adoption of policies such as establishing creative spaces, support programs, and relevant regulations, the local government has created an environment conducive to the development of the creative economy sector. Relevant data shows an increase in the number of creative industry players, job opportunities, and the quality of products and services produced by creative industry players in DKI Jakarta.